The Samurai of Sales : The Path to True Sales Mastery. - Harris, Mitch; Hancock, David (Newburyport : Morgan James Publishing, 2018)
The goal of The Samurai of Sales is to give the reader an arsenal of real life selling skills that he can use to generate massive sales and consistently outperform the competition, while cultivating the realization that when done properly, being in professional sales is one of the most amazing privileges on the planet.
Intro -- Title -- Copyright -- Contents -- Foreword -- Acknowledgments -- Warning -Disclaimer -- Introduction -- The Samurai -- 1. Conditioning Your Mind To Stay The Course -- 2. Your Beliefs: The Pain/Pleasure Navigator -- 3. Grab Your Prospect's Attention: Identifying The Barrier -- 4. Qualifying Your Prospect With Direction And Purpose -- 5. Slicing Through Objections: Part I -- 6. Slicing Through Objections: Part II -- 7. Defending Your Fee -- 8. The Power Of Getting Clear -- 9. Samurai Toolbox -- 10. The Fortune Is In The Follow Through -- Final Thoughts -- About The Author: Mitch Harris -- Quick Order Form.
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Selling; Vente; selling; Selling